Germany’s Tourism Sector: An Interdisciplinary Analysis of Growth and Sustainability (The Peerian Journal, 2025)
German tourism is one of the European leaders. However, due to Coviq-19, there was a strong dip in this industry. For example, in 2020, the tourist flow fell to 12mln, and in 2021-to 11 million. It should also be noted that the Germans are digitizing this area, and through this they take a fundamental place in solving future risks and current problems. This article focuses on the main aspects of German tourism-economic impact, sustainable tourism, digital transformation in mainly 2018-2022. Applied studied research this area illustrates trends, problems and opportunities.